Challenges on the way to a circular economy from the perspective of the Austrian manufacturing industry - Holly, Fabian; Kolar, Guenther; Berger, Manuel; Fink, Stefan; Ogonowski, Philip; Schlund, Sebastian (Frontiers in Sustainability, 2023)
Circular economy has become a prominent topic in scientific discourse and has gained significant presence as a strategic factor for business and industry. Both, as crucial enabler of a sustainable economy, and as lever for overcoming resource dependencies. Previous studies have identified multiple benefits of implementing circular principles, as well as enablers for a transformation to circular economy. However, studies with a focus on a specific industry and regional context that offer practical guidance for the transformation to a circular economy are still somewhat underrepresented. This paper addresses this gap by analysing major obstacles to a transformation to circular economy, in the context of the Austrian manufacturing industry. It is based on a literature review, in which 369 articles were reviewed, complemented by a structured online survey in which 229 managers from 192 companies in the manufacturing industry participated. In the survey, the obstacles were ranked according to their relevance on two levels: assessing ten clusters of obstacles on a higher level, followed by a deep-dive evaluation of specific obstacles within the clusters. Based on the research findings, it is evident that the circular economy plays a significant role in long-term corporate success and most surveyed companies recognize its strategic importance. The results also reveal that market and customer demand are the biggest drivers of a transformation to circular economy, followed by general concerns about the environment and regulatory pressure. The biggest barriers on the way towards circular economy are the need for more financial government support, challenges with setting up an effective circular supply chain, economic challenges resulting from customer behaviour and barriers in the redesign of products. The interdisciplinarity of the challenges leads to a high complexity in the transformation process. This means that most of the major barriers are external, and therefore companies cannot tackle these barriers by themselves. Governments should consider developing more incentive systems to support companies in their transition to the circular economy. To effectively navigate the transition, companies should adopt integrated strategies that encompass supply chain optimization, in-depth analysis of customer buying behaviours, and investment in sustainable and recyclable product design.